Regional economic resilience: exploring industrial decline in Bulawayo Metropolitan Province, Zimbabwe - Gambe, Tazviona Richman (Stellenbosch : Stellenbosch University, 2020)
Thesis (DPhil)--Stellenbosch University, 2020.